Atomistic approach for predicting mechanical properties and creep behavior of graphene reinforced natural rubber composites. (1st January 2023) - Hussain, Syed Asad; Sharma, Sumit; Patel, Pramod Rakt
Abstract: Graphene has proven to be one of the finest nanomaterials for rubber. In the present study the effect of volume fraction and functionalization of graphene sheets on the mechanical properties and creep behavior of natural rubber (NR) composites has been predicted using the molecular dynamics approach. The properties of NR nanocomposite with the graphene sheet volume fractions of 2.5%, 4.72%, and 11.35% have been compared with the properties of pristine NR. It was observed that the values of Young's modulus, bulk modulus, and shear modulus were increased up to 104%, 68.40%, and 17.5% respectively for the NR nanocomposite with the reinforcement of 11.35% of graphene compared to pristine NR. The ultimate tensile strength was also increased up to 46% with a higher volume fraction of the graphene sheet. The carboxyl and ester functional groups were used for the functionalization of the graphene sheet. Among the two groups, it was observed that the carboxyl group functionalized graphene sheet provided a better result than the ester group functionalized graphene sheet reinforced NR nanocomposite. The results showed that the introduction of graphene sheets improved the creep resistance of NR nanocomposites significantly. The pristine NR reached the failure stage in just 600 ps for the stress level of 140 MPa, whereas the NR nanocomposite with an 11.35% volume fraction sustained a higher stress level of 160 MPa and has not shown any sign of failure, even after the simulation time of 1000 ps.